The Prospect of Geotourism in the Cycloop Mountains Conservation Area Papua. Issue 1 (January 2022) - Setiadji, P; Sulistyantara, B; Pramudya, B; Suwardi
Abstract: The Cycloop mountains in Papua are a nature reserve conservation area that has diverse geology, biology and culture. This paper discusses the prospects of geotourism in Cycloop mountains based on a method of analyzing the community acceptability and tourists preferences, likewise the geosite attraction and geotourism sustainability. The results of analysis indicates that a) village communities in surrounding conservation area accept and wish to get involved in natural activities; b) local tourists are very dominant and motivated on outdoor recreation in groups; c) identified geosites has classified as from Quite Interesting to Interesting based on the index of attractiveness; and d) geotourism activity in the mountains Cycloop is categorized Quite Sustainable reviewed from the environment, society, economy and governance dimension. The exploration and the geological conservation to be the reliable activities in organizing the geotourism. Geotourism is likely to be applied to the conservation area as a form of implementation of the sustainable tourism concept.